Case report: Metastatic myxoid liposarcoma arising from the right atrium extends as cardiac tamponade—A rare case of atrial oncology - Thoddi Ramamurthy, Muralidharan; Kumar Balakrishnan, Vinod; Sunny, Sini; Rajkumar, Abinayaa; Sundaram, Sandhya; Krishnamurthy, Preetam; Boopathy Senguttuvan, Nagendra; Murali, Arunan; Santhosham, J. D. Roy; Periandavan, Kalaiselvi; Rajasekaran, Namakkal S. (Frontiers in Cardiovascular Medicine, 2023)
The reported incidence of liposarcomas in 2,000 cases annually results in about 30% of myxoid liposarcomas. Cardiac myoxid liposarcomas are very rare; their presentation could be cardiac tamponade, due to direct compression of the tumor and/or pericardial effusion. In this report, we describe a patient who presented with pericardial effusion secondary to myoxid liposarcomas from the right atrium, an extremely rare presentation of liposarcomas in the heart. We also present non-invasive imaging through echocardiography, CECT thorax and FDG PET scans, followed by a CT-guided mass biopsy. Histopathology of the right atrial mass demonstrated myxoid liposarcoma positive for the S100 tumor marker.